Cyber Crime Against Women's Personal Data on Online Platforms and The Role of PDP Laws - Rosyidah, Ambar Alimatur; Fajriyah, Farah; Rahayu, Rahayu (JURNAL KOMUNIKASI INDONESIA, 2024)
The presence of online platforms such as financial technology lending platforms is like a double-edged knife for women. These platforms pave the way for restrictions on women accessing loans. However, the use of fintech poses risks to women. They become victims of cybercrime with the existence of desk collectors who collect online loans and the third party who use the women's data. This study aims to examine the cybercrime implications of using fintech experienced by women related to fintech lending and then explore the role, data protection, and scope of the PDP Law as a solution. This study uses Qualitative Content Analysis (QCA) with the Tripartite Cybercrime Framework (TCF) from Ibrahim (2019) and Lazarus (2022) to analyze the problem. According to the author's criteria, the research data is from 15 women's complaint letters against fintech lending platforms that we obtained through the mediakonsumen.com website from 12 September 2020 to 8 November 2022. The PDP law, LBH reports, press releases, and relevant news media complement the data. These letters show five categories of women's experiences with online loan desk collector billing: online fraud, unauthorized transmission and use of personal data, identity theft, cyberbullying, and online harassment. This research also obtains socio-economic and psychosocial blending motives from online loan desk collectors. The core problem in online loan cases is ownership and access to personal data. Nevertheless, the PDP Law does not cover fundamental rights to data security, namely privacy rights and the victim's right to recovery.